Analisis Yuridis Kekuatan Hukum Pengajuan Permohonan Renvoi Prosedur Oleh Kreditor Yang Didasarkan Kepada Audit Internal Perusahaan Kreditor : Studi Putusan Mahkamah Agung No. 617.K/Pdt.Sus.Pailit/2018 - Wira Arizona (USU LAW JOURNAL, 2019)
Abstract. This is a normative juridical research which studies the Law No.37/2004 on Bankruptcy, PKPU (Suspension of Debt Payment Obligation), and the Verdict of the Supreme Court of the Republic of Indonesia No. 617.K/Pdt.Sus.Pailit/2018. This research is analytically descriptive. It employs library research and qualitative analysis. The internal auditor who has recalculated all receivables of PT.Pertamina EP from PT.Geo Cepu Indonesia as a bankrupt debtor found out differences in the amount of the debtor's debt/receivables from the amount that had previously been acknowledged and it submitted a request for renvoi based on their recalculation. According to Article 115-118 of the Law No. 37/2004 on Bankruptcy and PKPU, any changes of amount of debt/receivables of a bankrupt debtor or creditor are obliged to firstly get an approval from the bankrupt debtor or a verification made by a curator who will request for renvoi, and is obliged to be well recorded by the curator. The consideration of the Judges of the Supreme Court who objects the cassation of renvoi requested by PT Pertamina EP is right and proper because the renvoi should have been requested by firstly verified by and the bankrupt debtor, and supported by authentic evidence.   Keywords: renvoi, bankruptcy, and internal auditor